The Role of Social Media towards Competitiveness in Food and Beverage MSMEs - Dema Puteri Ayu Cahyani; R Deni Muhammad Danial; Kokom Komariah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Competitive advantage is where a company can formulate strategies that are placed in a way that is more profitable than competitors. This research was conducted at food MSME companies in Sukabumi City, the purpose of this study was to understand and the influence of social media on competitive advantage. With the desire to realize competitive advantages in Food and Beverage MSMEs in Sukabumi City, a company that has advantages in its field is created and has featured in the eyes of consumers to win the market competition. The data analysis technique used is simple linear regression using a quantitative approach. With 40 respondents, namely the owners or managers of Food and Beverage MSMEs using the IBM SPSS Version 24 software. This research concludes that it shows the significant influence of social media variables on competitive advantage.